2021
DOI: 10.3389/fonc.2021.719896
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Targeted Therapy for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the common and fatal malignancies, which is a significant global health problem. The clinical applicability of traditional surgery and other locoregional therapies is limited, and these therapeutic strategies are far from satisfactory in improving the outcomes of advanced HCC. In the past decade, targeted therapy had made a ground-breaking progress in advanced HCC. Those targeted therapies exert antitumor effects through specific signals, including anti-angiogenesis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 185 publications
(243 reference statements)
1
27
0
1
Order By: Relevance
“…The partial success of SOR has generated enthusiasm in the development of new molecules to be used as first- or second-line agents for systemic treatment of HCC. Between 2017 and 2018, four drugs (Lenvatinib, Regorafenib, Cabozantinib, and Ramucirumab), were found to be effective and tolerated, and have been approved by the Food and Drug Administration (FDA) as first- or second-line therapeutic agents for HCC patients [ 4 , 5 , 7 , 8 ]. To minimize resistance that often occurs as a consequence of the multi-step nature of HCC pathogenesis, the use of multi-target and/or combined therapies are suggested as the optimal strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The partial success of SOR has generated enthusiasm in the development of new molecules to be used as first- or second-line agents for systemic treatment of HCC. Between 2017 and 2018, four drugs (Lenvatinib, Regorafenib, Cabozantinib, and Ramucirumab), were found to be effective and tolerated, and have been approved by the Food and Drug Administration (FDA) as first- or second-line therapeutic agents for HCC patients [ 4 , 5 , 7 , 8 ]. To minimize resistance that often occurs as a consequence of the multi-step nature of HCC pathogenesis, the use of multi-target and/or combined therapies are suggested as the optimal strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [ 34 ] showed that reticulon 3-mediated activation of Chk2/p53 inhibit hepatocellular carcinogenesis. Moreover, some existing targeted therapies exert anti-HCC effects through specific signals, including anti-angiogenesis or cell cycle progression [ 35 ]. These results suggest that the pathological mechanism of HCC is very complex and involves the regulation of multiple genes and signaling pathways during progression.…”
Section: Discussionmentioning
confidence: 99%
“…The use of systemic therapies in combination with transarterial embolization techniques is an area of significant clinical and research focus [ 232 ]. Some of the many targeted systemic therapies that have been studied include, but are not limited to, MAPK Inhibitors, including sunitinib, sorafenib, imatinib, cabozantinib, lenvatinib, and selumetinib [ 233 , 234 ]. Others include immunotherapeutic agents such as ipilimumab, nivolumab, and pembrolizumab [ 235 , 236 , 237 ].…”
Section: New Developments and Future Directionsmentioning
confidence: 99%